Electro-oxidation of pyrite in sodium chloride solutions - Arslan, Fatma; Duby, Paul F. (Elsevier BV, 1997)
Abstract The mechanism of the electro-oxidation of pyrite in NaCl solutions was investigated. Laboratory work was carried out on the production of hypochlorite and the oxidation of pyrite in an electrochemical cell with a 10% sodium chloride electrolyte at 35–40°C. The production rate of hypochlorite was higher when the pH was not controlled than when it was maintained at the initial value of about 6.5. Pyrite was oxidized by the electrochemically generated hypochlorite, with an overall current efficiency of about 97%. The oxidation rate was directly related to the current and it was not affected by the pulp density.